Identifikasi Cemaran Mikroplastik pada Ikan Nila (Oreochromis niloticus) dan Ikan Puyau (Osteochilus vittatus) di Perairan Waduk Benanga, Samarinda - Yasmin Athirah Ramadhan; Masitah Masitah; Ruqqoyah Nasution; Nelda Anasthasia Serena (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Benanga Reservoir in Samarinda serves as a water source, river conservation area, and fishery location that supports local subsistence and commercial activities. However, the suboptimal management of plastic waste around Benanga Reservoir increases the risk of microplastic pollution that threatens human health and food security through fish consumption. This study aims to identify the types and amounts of microplastic contamination in Tilapia (Oreochromis niloticus) and Puyau (Osteochilus vittatus) in Benanga Reservoir waters. The research method is quantitative-descriptive exploratory. Fish samples were taken by purposive sampling method at 4 station points using a net (gillnet), the gills and digestive tract were destroyed using 10% KOH and flotation with 0.9% NaCl to be observed using a light microscope with the help of optilab viewer. Data were analyzed using descriptive statistics. Analysis of 12 fish samples showed the presence of microplastic contamination in all samples with a total of 155 particles including fiber, film, fragment, and pellet forms with various colors and sizes. The average abundance of tilapia is 11.4 particles/tail, while in puyau fish it reaches 14 particles/tail. Cumulatively, the level of microplastic contamination in puyau fish (98 particles) was identified as higher than in tilapia (57 particles), with fiber particles predominating in both species. The presence of microplastics in this local fish population emphasizes the urgency of waste management and pollution mitigation to ensure food security and ecosystem integrity in the Benanga Reservoir.